2010
DOI: 10.1371/journal.pone.0009480
|View full text |Cite
|
Sign up to set email alerts
|

Role of Spastin in Apical Domain Control along the Rhabdomere Elongation in Drosophila Photoreceptor

Abstract: BackgroundMutations in spastin are the most common cause of hereditary spastin paraplegia, a neurodegenerative disease. In this study, the role of spastin was examined in Drosophila photoreceptor development.Methodology/Principal FindingsThe spastin mutation in developing pupal eyes causes a mild mislocalization of the apical membrane domain at the distal section, but the apical domain was dramatically reduced at the proximal section of the developing pupal eye. Since the rhabdomeres in developing pupal eyes g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Immunohistochemistry: Fluorescent immunostaining of imaginal discs and pupal eyes were carried out as reported [9][10][11][12][13][14][15]. The following primary antibodies were used: mouse anti-a-Spectrin (Developmental Studies Hybridoma Bank), 1:25; rat anti-Elav (Developmental Studies Hybridoma Bank), 1:25.…”
Section: Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry: Fluorescent immunostaining of imaginal discs and pupal eyes were carried out as reported [9][10][11][12][13][14][15]. The following primary antibodies were used: mouse anti-a-Spectrin (Developmental Studies Hybridoma Bank), 1:25; rat anti-Elav (Developmental Studies Hybridoma Bank), 1:25.…”
Section: Geneticsmentioning
confidence: 99%
“…The pupal eye development was utilized for the instructor's main research material for the last 16 years. The instructor has analyzed cell polarity, cell junctions, and cytoskeletons using this important organogenesis model system [9,10,[12][13][14][15][22][23][24][25][26][27].…”
Section: Exercises 8-10: Pupal Eye Developmentmentioning
confidence: 99%
“…The microtubule regulators and microtubule-dependent motors were found to be involved in photoreceptor cell polarity in pupal photoreceptors (Chen et al, 2010(Chen et al, , 2011League and Nam, 2011;Mui et al, 2011;Mukhopadhyay et al, 2010;Nam, 2013Nam, , 2015. Therefore, the Tau might have a role in a microtubule-based trafficking and/or trafficking of cell polarity proteins as a microtubule stabilizer (Doerflinger et al, 2003;Weingarten et al, 1975;Witman et al, 1976) in photoreceptor cell polarity.…”
Section: Mutational Analysis Of Tau In Drosophila Pupal Photoreceptorsmentioning
confidence: 99%
“…Recently, we identified the specific localization of stabilized/ acetylated microtubule structures in developing Drosophila pupal photoreceptors ( Figure 1) (Chen et al, 2010). Recently, we identified the specific localization of stabilized/ acetylated microtubule structures in developing Drosophila pupal photoreceptors ( Figure 1) (Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…1) [13]. It was also found that Spastin, a microtubule-severing AAA ATPase involved in constructing neuronal and non-centrosomal microtubule arrays, helps control the apical localization of Crb [13].…”
Section: Introductionmentioning
confidence: 99%